STRATEGY OF PUBLIC SUPPORT FOR AGRICULTURE AND RURAL DEVELOPMENT. ASSUMPTIONS AND PRACTICE - Jan Misiąg; Wojciech Misiąg (Polityki Europejskie, Finanse i Marketing)
The aim of the article is to confront the arrangements of official strategy papers concerning agricultural and rural development, including the performance indicators, with the data illustrating the real policy pursued in this area and the effects of this policy. The content of key strategy papersas well as relevant data from the Central Statistical Office and the Ministry of Finance were also analysed. As a result, it was found that: (1) the indicators of objectives focused on supporting agriculture and rural areas adopted in analysed strategies cannot be used to interpret a coherent concept of the policy towards rural areas and agriculture; (2) there are inconsistencies between the arrangements of different strategies; (3) public support was aimed primarily at improving the income situation of farmers, to the detriment of achieving such objectives as improvement of agrarian structure and efficiency of farms, improvement of living conditions in the countryside and more effective environmental protection.